Modeling And Optimization Of Principal Supervision (Empirical Study Using The Pop-Sdm Approach At Vocational High Schools In Bogor Regency) - Gugun Gunadi; Soewarto Hardhienata; Siti Pupu Fauziah (PT Publikasiku Academic Solution, 2024)
This study aims to find strategies and ways to improve the effectiveness of principal supervision by examining other variables that have a positive and dominant influence on the effectiveness of principal supervision. From the qualitative research that has been carried out, different variables are Servant leadership and organizational culture as exogenous variables and organizational climate and personality as entering variables. The strategies and methods found were recommended to related parties, namely teachers, school principals, school supervisors, education offices, and the Ministry of Education and Culture. This study uses a combination of Correlation Research and SITOREM Analysis. This joint research methodology uses a correlation research flow, which is analyzed using SITOREM analysis. The residents in the study are all supervisors and principals of vocational schools in Bogor Regency. The sampling technique in this study uses a proportional random sampling technique, which collects data by taking a proportional population to be used as a sample. The formula used to determine the sample uses the Slovin formula with a margin of error of 5%. The study's conclusion showed a positive and significant influence of serving leadership, personality, and organizational climate on the effectiveness of principal supervision.